Learning style tendencies based on fleming’s VARK learning style among TVET students - Razali, N. S. M.; Ahmad, F.; Hamzah, N.; Wan Hassan, W. A. S.; Baharudin, S. M. (2021)
This study aims to identify learning style tendencies based on the Fleming’s VARK learning style of TVET students. This study uses a questionnaire approach to assess TVET students' learning styles based on Fleming’s visual, auditory, writing or reading and kinesthetic learning styles. The study population is technical students of FPTV, UTHM and the selected sample consists of 53 students from various fields namely General Machining (BBA), Welding and Metal Fabrication (BBD), Electrical & Electronics (BBE) and Creative Multimedia (BBF) who took the subject BBD10803 Information Technology in Education at Universiti Tun Hussein Onn Malaysia. The results of this study indicate that the most preferred Fleming’s VARK learning style is a visual learning style.